The role of environmental factors on disease and transmission of infectious diseases - Gifari, Rizki Muhammad; Zubir, Arina Azmina Ahmad (Environmental and Toxicology Management, 2024)
Infectious diseases remain a major global health problem, with environmental factors playing a significant role in the transmission and burden of disease, especially in densely populated areas. This literature review aims to evaluate the impact of environmental factors on infectious diseases. Data were collected from previous studies through platforms such as Google Scholar. The results showed that poor environmental conditions such as air pollution, lack of access to clean water, inadequate sanitation, and poor waste management contribute to increased incidence of diseases such as ARI, tuberculosis, and diarrhea. The studies analyzed highlighted significant associations between these environmental factors and health outcomes. This review underscores the need for targeted interventions to improve environmental conditions and reduce the burden of infectious diseases in communities. By understanding the relationship between environmental factors and disease transmission, we can develop effective prevention strategies to reduce exposure to pathogens and improve public health.